Graduate Students' Perspectives on Obtaining a Master's of Science in Respiratory Care. - Koster, Megan S.; McHenry, Kristen L.; Caldwell-Chadwick, Benjamin G.; Null, Megan M. (Respiratory Care, 2025)
Background: There has been a push toward degree advancement throughout respiratory care (RC), with many academic institutions creating graduate-level programs. However, many practitioners are apprehensive about advancing their degrees past the entry-into-practice level. Little research exists regarding the benefits of a graduate-level degree in RC. Methods: A web-based survey was developed to identify the perceived benefits of completing a master's of science in RC (MSRC) program. Graduates from 7 MSRC programs were asked to identify how efficacious the program was in preparing them for new or expanded roles, what types of financial support were received, whether there exists a financial benefit to obtain the degree, and whether the degree supported professional advancement. Two hundred ninety-nine graduates were invited to complete the anonymous web-based survey. One hundred one surveys were initiated, and 98 (32.8%) responses were analyzed. Results: Seventy-two percent of respondents indicated personal motivation for pursuing a graduate-level degree as well as a desire to stay in the field; 89% of respondents indicated that the program prepared them to assume new or expanded roles, and 58% had experienced advancement. Forty-five percent of respondents did not receive tuition reimbursement for degree advancement, and 88% did not receive any scholarship support toward the degree. Finally, graduates reported an average increase in salary of approximately $12,000. Conclusions: Attainment of a graduate-level RC degree through degree advancement remains reliant on intrinsic motivation. Although over half of respondents indicated receiving tuition support through an employer, opportunities continue to exist to increase financial support for clinicians to advance their education beyond the clinical requirements of licensure. Graduates indicated that earning the degree supported educational development, contributed to new or advanced roles, and contributed to a tangible increase in annual salary.